The role and effectiveness of Special Economic Zones in Tanzania - Abel Kinyondo; Carol Newman; Finn Tarp (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2016)
Special Economic Zones (SEZs) have been successfully used as an industrial policy tool in many countries. Efforts to create SEZs in Tanzania began in 2002, and were stepped up through the establishment of the Export Processing Zone Authority (EPZA) in 2006. A number of state-run zones are now in existence. Little is known, however, about how successful they have been. This paper aims to help fill this gap by exploring the role of state-owned SEZs in Tanzania. The focus is on understanding the nature and extent of interactions between firms and their employees within zones, the extent to which zones facilitate technology transfers, and the perceived benefits and constraints associated with operating with zones. We also examine the functioning of the EPZA and the bureaucratic structure surrounding the operation of zones.
Keywords: L3; L5; L7; O2; 330; economic zones; performance; public policy; Tanzania